2019
DOI: 10.31580/jpvai.v2i4.1151
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Leadership Enhance Innovation: A Systematic Review of Past Decade

Abstract: The globalization has made it manadory for the industries to introduce novel ideas in the products and services that they offer, and that is due to the rapidly increasing competition. For this prevaling innovation, it is very important for the management to adopt the right type of leadership. A managerial perception having the aim of producing constant and better results and reducing turnover and absenteeism of employees and last but not the least hastening the inventions and new creations, is called sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In retrospect, the studies on innovation have identified a strong link between leadership styles and organizational innovation (Haroon et al, 2019). The frugal innovation capability of a firm is determined by intellectual capital and leadership characteristics (Cuhadar and Rudnák, 2022).…”
Section: Literature Review and Hypotheses Development Frugal Innovati...mentioning
confidence: 99%
“…In retrospect, the studies on innovation have identified a strong link between leadership styles and organizational innovation (Haroon et al, 2019). The frugal innovation capability of a firm is determined by intellectual capital and leadership characteristics (Cuhadar and Rudnák, 2022).…”
Section: Literature Review and Hypotheses Development Frugal Innovati...mentioning
confidence: 99%